2022
DOI: 10.3390/en15062144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Local Emergency Demand Response Programs on the Operation of Electricity and Gas Systems

Abstract: With increasing attention to climate change, the penetration level of renewable energy sources (RES) in the electricity network is increasing. Due to the intermittency of RES, gas-fired power plants could play a significant role in backing up the RES in order to maintain the supply–demand balance. As a result, the interaction between gas and power networks are significantly increasing. On the other hand, due to the increase in peak demand (e.g., electrification of heat), network operators are willing to execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Demand Side Response (DSR) is a common term for technologies that enable the temporal shifting of various types of electricity demand in response to system conditions. It is demonstrated in [94] that DSR can reduce the operational cost of gas and electricity networks by up to 11%. Recent research has shown that DSR can support a more cost-effective transition of energy systems toward the zero-carbon objective [88].…”
Section: Demand Side Responsementioning
confidence: 99%
“…Demand Side Response (DSR) is a common term for technologies that enable the temporal shifting of various types of electricity demand in response to system conditions. It is demonstrated in [94] that DSR can reduce the operational cost of gas and electricity networks by up to 11%. Recent research has shown that DSR can support a more cost-effective transition of energy systems toward the zero-carbon objective [88].…”
Section: Demand Side Responsementioning
confidence: 99%
“…Equations ( 19)-( 22) present the constraints imposed by MG loads, load shedding, and critical loads on the distribution feeders [33][34][35]. (20) exhibits the load control mechanism in the microgrids, whereas constraint (21) specifies the controllable load limits at different levels.…”
Section: Demand Constraintsmentioning
confidence: 99%
“…The demand-side response and economic analysis of energy storage configuration can be added in the next step. The smart technologies used in [34,35] can be integrated into the method of this paper, allowing the ESS configuration to achieve a balance between technical, economic, and policy.…”
mentioning
confidence: 99%